Problems and solutions for the management of a unitary system of landslide monitoring networks: an experience in North Italy - Dei Cas, Luca; Pastore, Maria Luisa; Bonetti, Dennis; Ferrarini, Francesco (Italian journal of engineering geology and environment, 2022)
International scientific studies show that landslides are widespread throughout Europe, especially in Italy (Herrera et alii, 2018; Trigila et alii, 2007). Due to the phenomenon high dimension, it’s not possible to act in all the areas with structural operations to reduce the landslides risk. For this reason, the geological monitoring networks represent an efficacious and cost-effective system to protect the population. ARPA Lombardia, with Geological Monitoring Centre (CMG), has worked for the last years for the management of dozens of early warning geological monitoring networks. CMG has been monitoring a total of 44 landslide areas and has been collecting and analysing about 25 million data for the last years. These data are acquired by sensors every 10 or 30 minutes. This paper will take in consideration the essential and critical aspects linked to the planning, integration and unitary management of numerous monitoring networks to control landslides. The CMG’s experience has shown how the unitary management of the warning systems of multiple monitoring networks is the ideal method to manage landslides problem and reduce hazard. This paper highlights how the technician’s formation on landslides and geological monitoring networks has allowed better management of the landslide risk problem. Finally, it is quantitatively demonstrated that management costs show significant reductions after the implementation of this unitary management.